Fructose metabolism is unregulated in cancers and placentae - Fuller W. Bazer; Guoyao Wu; Gregory A. Johnson (Experimental Biology and Medicine)
Fructose and lactate are present in high concentrations in uterine luminal fluid, fetal fluids and fetal blood of ungulates and cetaceans, but their roles have been ignored and they have been considered waste products of pregnancy. This review provides evidence for key roles of both fructose and lactate in support of key metabolic pathways required for growth and development of fetal-placental tissues, implantation and placentation. The uterus and placenta of ungulates convert glucose to fructose via the polyol pathway. Fructose is sequestered within the uterus and cannot be transported back into the maternal circulation. Fructose is phosphorylated by ketohexokinase to fructose-1-PO4 (F1P) by that is metabolized via the fructolysis pathway to yield dihydoxyacetone phosphate and glyceraldehyde-3-PO4 that are downstream of phosphofructokinase. Thus, there is no inhibition of the fructolysis pathway by low pH, citrate or ATP which allows F1P to continuously generate substrates for the pentose cycle, hexosamine biosynthesis pathway, one-carbon metabolism and tricarboxylic acid cycle, as well as lactate. Lactate sustains the activity of hypoxia-inducible factor alpha and its downstream targets such as vascular endothelial growth factor to increase utero-placental blood flow critical to growth and development of the fetal-placental tissues and a successful outcome of pregnancy. Pregnancy has been referred to as a controlled cancer and this review addresses similarities regarding metabolic aspects of tumors and the placenta.